Effect of Fiscal Decentralization, Provincial Minimum Wage, and Local Revenue on Income Inequality in Islamic Economic Perspective - Sholeah, Diah Aska; Fasa , Muhammad Iqbal; Kurniawan, Agus (Indonesian Journal of Islamic Economics and Finance, 2025)
This study aims to analyze the effect of fiscal decentralization, provincial minimum wages, and local revenue (PAD) on income inequality in the provinces on the island of Sumatra in the period 2018-2024, as well as review the findings in the perspective of Islamic economics. Income inequality in Indonesia, especially in the Sumatra region, is still a significant issue despite various decentralization policies and increased minimum wages. This research method uses a quantitative approach of panel data, which combines time series and cross section data. Data is obtained from the Central Bureau of Statistics and other reliable sources. The analysis was conducted using panel data regression model through Random Effect Model (REM) approach selected based on the results of Chow, Hausman, and Lagrange Multiplier tests. All testing was done using EViews software. The results of the analysis show that simultaneously, fiscal decentralization, provincial minimum wages, and PAD have a significant effect on income inequality, although the direction and significance vary between variables and provinces. In the Islamic economic perspective, the reduction of income inequality is part of the principle of distributive justice which is required to ensure welfare and avoid the accumulation of wealth in certain groups. Therefore, the implementation of fiscal and labor policies is expected to be in line with Islamic values, such as justice, equity, and alignment with the weak.